Implementation of augmented reality in an application to recognize traditional Papuan musical instruments as a medium for cultural preservation - Andi Roy; Tri Bata Biru Saputri; Muh. Fachruddin; Nur Sakinah (Institute of Computer Science (IOCS), 2026)
Traditional musical instruments of Papua represent a rich cultural heritage that faces a decline in public awareness due to limited access and physical preservation challenges. Most instruments are stored exclusively in cultural houses (Sanggar) or museums, isolating them from the younger generation who are deeply engaged with modern mobile technologies. This study aimed to develop and evaluate an Augmented Reality (AR)-based cultural preservation medium that improves public access to information on Papuan traditional musical instruments, specifically the Tifa, Tifa Titir, and Gong from the Fakfak region. The novelty of this study lies in its localized integration of three-dimensional visualization, authentic instrument sounds, and contextual cultural information into a mobile AR application designed for indigenous musical heritage preservation. Using a structured Waterfall development approach, cultural data were collected from local cultural custodians and transformed into interactive digital content. The application projects realistic 3D assets, plays authentic instrument sounds, and displays textual cultural information upon scanning unique physical markers. Black-box testing validated that all system features, including marker tracking, audio triggers, and page navigation, functioned successfully across various Android hardware environments. User satisfaction evaluations yielded an overall cumulative usability index of 90.35%, classifying the application as highly effective and user-friendly. This digital intervention bridges the gap between historical preservation and modern education, providing an accessible, interactive, and community-oriented model for cultural digitization and learning